2023
DOI: 10.1093/neuonc/noad025
|View full text |Cite
|
Sign up to set email alerts
|

Novel murine glioblastoma models that reflect the immunotherapy resistance profile of a human disease

Abstract: Background The lack of murine glioblastoma models that mimic the immunobiology of human disease has impeded basic and translational immunology research. We therefore developed murine glioblastoma stem cell lines derived from Nestin-CreERT2QkL/L; Trp53L/L; PtenL/L (QPP) mice driven by clinically relevant genetic mutations common in human glioblastoma. This study aims to determine the immune sensitivities of these QPP lines in immunocompetent hosts and underlying mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…), which showed in vivo therapeutic activity at 5 μg/dose ( Supplemental Figure 1 ; supplemental material available online with this article; https://doi.org/10.1172/JCI175033DS1 ). GL261 is an immunogenic model of glioblastoma that responds readily to immune checkpoint blockade ( 29 ), unlike human glioblastoma. In contrast, the QPP4 and QPP8 glioblastoma models are poorly immunogenic and resist both CTLA-4 and PD-1 blockade ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), which showed in vivo therapeutic activity at 5 μg/dose ( Supplemental Figure 1 ; supplemental material available online with this article; https://doi.org/10.1172/JCI175033DS1 ). GL261 is an immunogenic model of glioblastoma that responds readily to immune checkpoint blockade ( 29 ), unlike human glioblastoma. In contrast, the QPP4 and QPP8 glioblastoma models are poorly immunogenic and resist both CTLA-4 and PD-1 blockade ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…GL261 is an immunogenic model of glioblastoma that responds readily to immune checkpoint blockade ( 29 ), unlike human glioblastoma. In contrast, the QPP4 and QPP8 glioblastoma models are poorly immunogenic and resist both CTLA-4 and PD-1 blockade ( 29 ). Even in these models, we found that 2–3 doses at 5 μg of 8803 could elicit rejection in 56% (QPP4; P = 0.0003) to 100% (QPP8; P < 0.0001) of animals ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%